(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2017)
The major aim of this study is to ascertain the feasibility of using recycled products in the form of post-consumer material using different regrind ratios to produce new products without a significant reduction in product quality. Five regrind ratios were used in this study: 0%, 20%, 50%, 80% and 100%. The used products were collected from different public places in Misurata city-Libya. The properties under investigation are mass, shrinkage, color, and solid density. The results indicated to no remarkable change in the concerned properties.